Changes in plasma vascular endothelial growth factor at 8 weeks after sorafenib administration as predictors of survival for advanced hepatocellular carcinoma. Issue 2 (7th October 2013) - Tsuchiya, Kaoru; Asahina, Yasuhiro; Matsuda, Shuya; Muraoka, Masaru; Nakata, Toru; Suzuki, Yuichiro; Tamaki, Nobuharu; Yasui, Yutaka; Suzuki, Shoko; Hosokawa, Takanori; Nishimura, Takashi; Ueda, Ken; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND A new predictive biomarker for determining prognosis in patients with hepatocellular carcinoma (HCC) who receive sorafenib is required, because achieving a reduction in tumor size with sorafenib is rare, even in patients who have a favorable prognosis. Vascular endothelial growth factor (VEGF) receptor is a sorafenib target. In the current study, the authors examined changes in plasma VEGF concentrations during sorafenib treatment and determined the clinical significance of VEGF as a prognostic indicator in patients with HCC. METHODS Plasma VEGF concentrations were serially measured in 63 patients with advanced HCC before and during sorafenib treatment. A plasma VEGF concentration that decreased >5% from the pretreatment level at 8 weeks was defined as a "VEGF decrease." An objective tumor response was determined using modified Response Evaluation Criteria in Solid Tumors 1 month after the initiation of therapy and every 3 months thereafter. RESULTS Patients who had a VEGF decrease at week 8 (n = 14) had a longer median survival than those who did not have a VEGF decrease (n = 49; 30.9 months vs 14.4 months; P = .038). All patients who had a VEGF decrease survived for >6 months, and the patients who had both a VEGF decrease and an α‐fetoprotein response (n = 6) survived during the observation period (median, 19.7 months; range, 6.5‐31.0 months). In univariate analyses, a VEGF decrease, radiologic findings classified as progressive disease, and major vascular invasion were associated significantly with 1‐year survival; and, in multivariate analysis, a VEGF decrease was identified as an independent factor associated significantly with survival. CONCLUSIONS A plasma VEGF concentration decrease at 8 weeks after starting sorafenib treatment may predict favorable overall survival in patients with advanced HCC. Cancer 2014;120:229–237. © 2013 American Cancer Society.